Genome-wide association study in RPGRIP1(−/−) dogs identifies a modifier locus that determines the onset of retinal degeneration - Miyadera, Keiko (2011)
Cone-rod dystrophy (CRD) is a form of inherited retinal degeneration (RD) causing blindness in man as well as in several breeds of dog. Previously, a 44 bp insertion in RPGRIP1 (retinitis pigmentosa GTPase regulator interacting protein-1) was associated with a recessive early-onset CRD (cone-rod dystrophy 1, cord1) in a Miniature longhaired dachshund (MLHD) research colony. Yet in the MLHD pet population, extensive range of the onset age has been observed among RD cases, with some RPGRIP1(−/−) dogs lacking obvious clinical signs. Phenotypic variation has been known in human homologous diseases, including retinitis pigmentosa and Leber congenital amaurosis, indicating possible involvement of modifiers. To explore additional genetic loci associated with the phenotypic variation observed in MLHDs, a genome-wide association study was carried out using Canine SNP20 arrays in 83 RPGRIP1(−/−) MLHDs with variable ages of onset or no clinical abnormality. Using these samples, comparison of 31 early-onset RD cases against 49 controls (15 late-onset RD and 34 normal dogs combined) identified a strong association (P = 5.05 × 10(−13)) at a single locus on canine chromosome 15. At this locus, the majority of early-onset RD cases but few of the controls were homozygous for a 1.49 Mb interval containing ∼11 genes. We conclude that homozygosity at both RPGRIP1 and the newly mapped second locus is necessary to develop early-onset RD, whereas RPGRIP1(−/−) alone leads to late-onset RD or no apparent clinical phenotype. This study establishes a unique model of canine RD requiring homozygous mutations at two distinct genetic loci for the manifestation of early-onset RD.